?RESPONSE OF CHICKPEA TO NIPPING: Short Communication (Biological Sciences - PJSIR, 2000)
Chickpea (Cicer arietinum L) is the third important pulsecrop of Bangladesh pertinent to area and production. It isgrown on 0.74m hectares of land producing 0.54m tons ofgrain with an average yield of371 kg ha' (Anon 1996).